2023
DOI: 10.3390/jcm12093319
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Outcomes in Pediatric Patients One-Year Post-Total Pancreatectomy with Islet Autotransplantation after Early Pump Initiation

Abstract: We previously published that insulin pump initiation immediately after IV insulin therapy was associated with improved post-surgical glycemic outcomes compared to multiple daily injections (MDI) in pediatric patients following a total pancreatectomy with islet autotransplantation (TPIAT). We investigated metabolic outcomes of this population at one-year post-TPIAT to assess if the improved outcomes in the early pump group were sustained over time. We retrospectively reviewed 40 patients post-TPIAT previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…23 Transition to early insulin pump usage in children was associated with greater likelihood of insulin independence at 1-year follow-up. 65 In a large single-site study of TPIAT durability, insulin independence at 10 years was positively associated with age <18 years at the time of surgery and a higher transplanted islet mass. 26…”
Section: Postpancreatectomy Diabetes Mellitusmentioning
confidence: 98%
“…23 Transition to early insulin pump usage in children was associated with greater likelihood of insulin independence at 1-year follow-up. 65 In a large single-site study of TPIAT durability, insulin independence at 10 years was positively associated with age <18 years at the time of surgery and a higher transplanted islet mass. 26…”
Section: Postpancreatectomy Diabetes Mellitusmentioning
confidence: 98%
“…Despite its limitations, recent studies have shown that metabolic testing performed three months after TPIAT strongly correlated with later diabetes outcomes, offering a reliable prediction model that provides valuable prognostic insight early after TPIAT [64]. Furthermore, modified management protocols, including early use of insulin pumps post TPIAT in pediatric patients, have demonstrated enduring benefits [65,66].…”
Section: Total Pancreatectomy (Tp)mentioning
confidence: 99%